2012
DOI: 10.1177/193758671200500306
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical Simulation Centers to Test Design Interventions: A Pilot Study of Lighting and Color Modifications

Abstract: This study reinforces the use of validated survey tools to measure stress, alertness, and satisfaction. Results support human-centered design approaches by evaluating the effect on nurses in an experimental setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Some environmental factors can increase nurses' level of stress, which is associated with lower quality of care (Smith et al, 2001). Because the design of the built environment can impact the performance of the occupants, however, nursing stations can also create conditions in which nurses' performance can thrive (Grey, 2012).…”
Section: Nurses Nursing Stations and Communicationmentioning
confidence: 99%
“…Some environmental factors can increase nurses' level of stress, which is associated with lower quality of care (Smith et al, 2001). Because the design of the built environment can impact the performance of the occupants, however, nursing stations can also create conditions in which nurses' performance can thrive (Grey, 2012).…”
Section: Nurses Nursing Stations and Communicationmentioning
confidence: 99%
“…Past research analyzed the stimuli of patients to various colors but without conducting the study in a real-life setting [7,29,30]. While some other investigations focused on the effects of healthcare environment, in general evidence regarding the impact of col-Positive effect of colors and art in patient rooms on patient recovery after total hip or knee arthroplasty K original article ors on patients' postoperative rehabilitation is lacking [6,18].…”
Section: Discussionmentioning
confidence: 99%
“…Patient rooms. Gray et al (2012) used room simulations to measure self-reported nurse stress, alertness, and satisfaction. Blue spatial color patterning was used to organize equipment on the wall of a patient room.…”
Section: Color Studies In General Medical Settingsmentioning
confidence: 99%